Закономірності просторового розподілу ґрунтів та рослинного покриву балкових систем басейну р. Інгулець. балка “Зелена” - Smetana, O.M.; Smetana, M.G.; Krasova, O.O. (M.M. Gryshko National Botanical Garden of the NAS of Ukraine, 2009)
The regularity of plant and soil covers organization of experimental plot in gorge "Zelena" were investigated. Their connections and peculiarities of combine formation were studied.